2020
DOI: 10.35530/it.071.02.1793
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of textile materials with bioactive polymeric systems based on propolis and cinnamon essential oil

Abstract: In order to obtain the textile materials with potential for use in the treatment of inflammatory skin conditions, this study approached the laboratory experiments related to depositing by padding of oil-in-water emulsions type based on chitosan-propolis-cinnamon essential oil. In this regard, seven experimental variants of emulsions were prepared and then characterized by specific methods from physical-chemical and stability point of view. The chitosan-propolis- cinnamon essential oil-based emulsions were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Similar results can be seen in multifilaments containing natural compounds with myrrh and polymeric film containing cinnamon oil, myrrh, and rosin. After modifying multifilament yarns with natural compounds, the films also showed lower reflectance in the UV region [17,36,47]. The presence of compounds introduced into PLA multifilament yarns through the addition of rosin (i.e., B, C, E, and F) indicates a significant increase in absorption (and a decrease in diffuse reflection) in the wavelength ranging from 500 to 400 nm as well as broad and intensive absorption bands in the entire UV region (from 200 to 400 nm) of the recorded spectra.…”
Section: Optical Analysis Of Melt-spun Multifilament Yarnsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results can be seen in multifilaments containing natural compounds with myrrh and polymeric film containing cinnamon oil, myrrh, and rosin. After modifying multifilament yarns with natural compounds, the films also showed lower reflectance in the UV region [17,36,47]. The presence of compounds introduced into PLA multifilament yarns through the addition of rosin (i.e., B, C, E, and F) indicates a significant increase in absorption (and a decrease in diffuse reflection) in the wavelength ranging from 500 to 400 nm as well as broad and intensive absorption bands in the entire UV region (from 200 to 400 nm) of the recorded spectra.…”
Section: Optical Analysis Of Melt-spun Multifilament Yarnsmentioning
confidence: 99%
“…Similar results can be seen in multifilaments containing natural compounds with myrrh and polymeric film containing cinnamon oil, myrrh, and rosin. After modifying multifilament yarns with natural compounds, the films also showed lower reflectance in the UV region [17,36,47].…”
Section: Optical Analysis Of Melt-spun Multifilament Yarnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, application of nanotechnology has demonstrated that conventional textile products can be transformed into materials having an entirely new set of properties with an overall enhancement in the functionality too (Yuranova et al , 2006). To achieve the desired functionality, a range of materials from polymeric products (Chirilă et al , 2020; Tadesse et al , 2020) to metals in different forms (Balci et al , 2014) are reportedly used.…”
Section: Introductionmentioning
confidence: 99%
“…Biological macromolecules are non-toxic and degradable with natural biocompatibility, which become new materials resources for the development and utilization as functional agents. 17,18 Many biological macromolecules, including collagen, chitosan, and sericin, have been widely applied in the medical and cosmetics industry. [19][20][21][22][23][24][25] Collagen is a kind of macromolecular protein found in skin, blood vessels and bones, which obtained from different animals has good health function.…”
Section: Introductionmentioning
confidence: 99%